Case Report: Cutaneous Pleomorphic Lymphangiosarcoma in a Dog Exhibiting Features of Human Composite Hemangioendothelioma - Cook, Matthew R.; Lorbach, Joshua N.; White, Mary E.; Zann, Geoffrey J.; Cianciolo, Rachel E.; Selmic, Laura E.; Wavreille, Vincent; Kisseberth, William C. (Frontiers in Veterinary Science, 2021)
Background: Angiosarcomas are a broad category of vascular origin neoplasms that are poorly characterized in veterinary species. Lymphangiosarcoma (LAS) is an uncommon type of angiosarcoma reported in humans and canines arising from lymphatic endothelium. LAS can be differentiated from other angiosarcomas in dogs based on expression of Prospero-related homeobox gene-1 (PROX-1) or lymphatic vessel endothelial receptor-1 (LYVE-1). Composite hemangioendothelioma (CHE) is a rare angiosarcoma subtype described in people and characterized by a variable biologic behavior and infrequent metastasis. This variant of angiosarcoma histologically combines features of retiform hemangioendothelioma and epithelioid hemangioendothelioma. Information regarding the cytologic and histopathologic appearance and clinical course of dogs with vascular tumors that exhibit features of CHE are unknown. Here, we report a case of pleomorphic LAS with features of CHE arising in a dog and treated with surgery and adjuvant chemotherapy. Case presentation: A 10-year-old intact male Labrador retriever presented with an approximately 6-cm-diameter cutaneous mass caudal to the left elbow that was progressively growing over 1.5 years. On physical examination, palpable extensions were identified coursing proximally over the triceps with concurrent loco-regional peripheral lymphadenopathy. Fine needle aspirates (FNA) and cytologic assessment of the cutaneous mass, left prescapular, and accessory axillary lymph nodes reported that this appeared to be a metastatic epithelial neoplasm, although a mixed carcinoma or collision tumor could not be excluded. An incisional biopsy of the mass was submitted for histopathology and was consistent with a well-differentiated angiosarcoma with features of CHE. The neoplasm expressed vimentin, CD31, von Willebrand factor (vWf), and PROX-1, supporting the diagnosis of LAS. Complete staging was performed, and no additional metastatic lesions were identified. Left forelimb amputation and lymph node removal were performed. Based on the diagnosis of metastatic LAS, doxorubicin chemotherapy was administered. 7 months post-amputation, the tumor recurred at the amputation site without evidence of metastatic disease. Conclusion: This report describes a malignant, locally aggressive lymphatic origin vascular tumor in a dog, with features consistent with descriptions of CHE in humans. Cytologic features in this case were discordant with its true mesenchymal etiology, obfuscating diagnosis. The morphologic features of the mesenchymal neoplastic population and immunohistochemistry (IHC) labeling ultimately supported a diagnosis of pleomorphic LAS with features of CHE.